The Urgency of the Google Sites as Biology Learning Media Based on Digital Literacy - Lutfi, Anas; Sari, Indah Juwita; Camara, Jun S. (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
The advancement of information technology encourages teachers to be able to maximize the use of technological advances with the aim of achieving the standards of the learning process in educational institutions. The purpose of this paper is to analyze the need for the use of learning media on the Google Sites website based on digital literacy in biology material. This research uses qualitative methods. Therefore, this research uses descriptive qualitative research to describe a phenomenon that occurs in the field. The sample in the study was 1 biology teacher at a senior high school in Pandeglang, Indonesia and 62 students of grade 11 and 12 at a senior high school in Pandeglang, Indonesia. The research was conducted in May 2023 at at a senior high school in Pandeglang, Indonesia. In collecting data using techniques such as giving questionnaires to students, teacher interviews, and school observations. Analysis of data that has been obtained using stages consisting of data collection, data reduction, data presentation, and drawing conclusions. The results of this study found that 53.2% of students found it difficult to understand biology material due to lack of learning and learning media. So this needs analysis aims to find out the development of digital literacy-based google sites web learning media that will be developed as an alignment between the independent curriculum, learning variations, and digital literacy skills.